Inclusive-Based Deductive Training Model for Tour Guide in Goa Pindul - PRASETYO, Iis; DEWI, Adin Ariyanti; ROFIQ, Akhmad (Journal of Environmental Management and Tourism; Vol 15 No 2 (2024): JEMT, Volume XV, Issue 2(74), Summer 2024DO - 10.14505/jemt.v15.2(74).14, 2024)
Tourism is an important industrial sector for the country's economy. Yogyakarta is a province with numerous tourist attractions, including Pindul Cave. Pindul Cave is a popular tourist destination with both domestic and international visitors. Tourism managers must be able to provide the best facilities for a wide range of visiting tourists, including those with special needs (disabilities), given the growing number of tourists. The goals of this study are to 1) find a consensual model of deductive training for tourist guides at Pindul Cave that is inclusive, and 2) to create an inclusive tourist guidebook. This is a multi-year study, and in the first year, the research team only reached the limits of identification and conceptual model. The research method used was qualitative, with focus group discussions with targets. Data was collected using observation, focus group interviews, documentation, and questionnaires. Meanwhile, four data analysis techniques are used: data collection, data reduction, data presentation, and conclusion. The research findings yielded a conceptual model of inclusive-based training for tour guides that includes three components: (1) identifying needs, (2) training planning, (3) implementing training programs, and (4) evaluating training. Meanwhile, the guidebook will be used for testing in the second year of this study.